PENGARUH FAKTOR FUNDAMENTAL, RISIKO SISTEMATIS DAN INDIKATOR MAKRO PADA RETURN - Sri Isworo Ediningsih; Wahyu Endrian (Akademi Akuntansi YKPN Yogyakarta, 2008)
The purpose of this research is to analyse the impact of fundamental factors, systematic risk and macro indicators on stock return. Sample of this research are 21 LQ-45 firms at Jakarta Stock Exchange over the 2003-2006 period. The method used in the analysis is multiple regression. The results of this research show that: 1) Simultaneusly fundamental factors, systematic risk and macro indicators, significantly influenced stock return, 2) Partially EPS as proxy of fundamental factors, systematic risk and exchange rate as proxy of macro indicators significatnly influenced but CR as proxy fundamental factors is not significantly influenced stock return, and 3) Systematic risk dominantly influenced stock return.Keywords: fundamental factors, systematic risks, macro indicators, and stock return